2016
DOI: 10.1016/j.circir.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Cambios urodinámicos posteriores a cirugía de ampliación vesical por vejiga neurogénica en pacientes pediátricos con mielomeningocele

Abstract: Augmentation cystoplasty with sigmoid colon significantly improved urodynamic parameters, such as bladder accommodation and filling pressure in children with myelomeningocele-associated neurogenic bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
2
0
1
Order By: Relevance
“…Compliance, end filling pressure, and continence also improved substantially. These results are consistent with the findings of other studies[ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 94%
“…Compliance, end filling pressure, and continence also improved substantially. These results are consistent with the findings of other studies[ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 94%
“…[ 40 ] Similar results were noted in a series of children with neurogenic bladder due to meningomyelocele with filling pressure reducing from 41 to 11 cm H 2 O. [ 41 ] In contrast, Vainrib et al . showed that 11% of adult meningomyelocele patients had unsatisfactory compliance at a mean follow-up of 10.4 years.…”
Section: Literature On Follow-up Urodynamicssupporting
confidence: 63%
“…При наличии остатка мочи в объеме более 10 мл, особенно на фоне пиелоэктазии или мегауретера, необходимо устанавливать постоянный уретральный катетер (лучше использовать катетер Фолея соответствующего размера) на фоне антибактериальной терапии. Ребенок должен находиться под наблюдением уролога начиная с первого месяца жизни [1, 11,12].…”
Section: резюме _____________________________________________________...unclassified